Analisis Persepsi Guru Sekolah Dasar Mengenai Digitalisasi Dalam Proses Pembelajaran - Ria Triayomi; Petrus Murwanto; Agnes Fibriana Kurniawati (CV. Creative Tugu Pena, 2024)
This study aims to analyze the perceptions of elementary school teachers regarding digitalization in the learning process towards the use of technology in learning, the challenges faced in integrating technology, the role of school leadership in digitalization of learning, teachers' expectations of digitalization in learning. The sample in this study involved 15 English teachers from 30 high schools and equivalent in Pekanbaru city. The research method used is descriptive qualitative research. Data obtained from the questionnaire were analyzed by data reduction, data display, and drawing and verifying conclusions. For data validation using data triangulation techniques. The results of this study indicate that although most elementary school teachers have a positive perception of digitalization in learning, there are various challenges that need to be overcome.